2007
DOI: 10.1086/521016
|View full text |Cite
|
Sign up to set email alerts
|

Population Synthesis of Radio and γ‐Ray Millisecond Pulsars from the Galactic Disk

Abstract: We present results of a population synthesis of millisecond pulsars from the Galactic disk. Excluding globular clusters, we model the spatial distribution of millisecond pulsars by assuming their birth in the Galactic disk with a random kick velocity and evolve them to the present within the Galactic potential. We assume that normal and millisecond pulsars are standard candles described with a common radio luminosity model that invokes a new relationship between radio core and cone emission suggested by recent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
160
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(173 citation statements)
references
References 64 publications
(99 reference statements)
12
160
0
1
Order By: Relevance
“…In particular, it was suggested that deep radio searches of Fermi-LAT sources could discover MSPs, leading to detection of their γ-ray pulsations [42]. A Pulsar Search Consortium (PSC) undertook searches at radio and X-ray wavelengths at the positions of unidentified γ-ray sources that were non-variable and had hard spectra with high-energy cutoffs.…”
Section: The Fermi Treasure Mapmentioning
confidence: 99%
“…In particular, it was suggested that deep radio searches of Fermi-LAT sources could discover MSPs, leading to detection of their γ-ray pulsations [42]. A Pulsar Search Consortium (PSC) undertook searches at radio and X-ray wavelengths at the positions of unidentified γ-ray sources that were non-variable and had hard spectra with high-energy cutoffs.…”
Section: The Fermi Treasure Mapmentioning
confidence: 99%
“…Several models have been proposed over the years to characterize the population of pulsars in the Galaxy, either ordinary (Lyne et al 1985;Yusifov & Küçük 2004;Lorimer et al 2006;Faucher-Giguère & Kaspi 2006), millisecond (Lorimer et al 1996;Cordes & Chernoff 1997;Story et al 2007), or both (Lyne et al 1998;Faucher-Giguère & Loeb 2010).…”
Section: Model For the Galactic Population Of Pulsarsmentioning
confidence: 99%
“…The luminosity distribution of ordinary pulsars has been modeled by one or two power laws (Lyne et al 1998;Guseinov et al 2003). Models where the luminosity distribution depends on the pulsar period and its derivative have also been considered, for both millisecond and ordinary pulsars (Story et al 2007). The flux A7, page 8 of 11 density was computed by multiplying the luminosity by the square of the distance to the synthetic pulsar.…”
Section: Model For the Galactic Population Of Pulsarsmentioning
confidence: 99%
“…Other authors have used different definitions of κ(x) and ω CR (e.g., Harding 1981;Daugherty & Harding 1982;Cheng & Zhang 1996;Story et al 2007;Venter et al 2009b):…”
Section: Standard Cr Expressionsmentioning
confidence: 99%
“…Such computationally expensive calculations are needed, for example, if one intends to study radiation properties of a sizable population of pulsars (e.g., Story et al 2007), or for examining the cumulative emission generated by an ensemble of MSPs believed to be responsible for the HE emission recently detected by Fermi-LAT from several globular clusters (GCs; Abdo et al 2009Abdo et al , 2010c. In addition to CR calculations, this also holds for computing X-ray to gamma-ray SR spectral components.…”
Section: Introductionmentioning
confidence: 99%